Invasive non-native plants have a greater effect on neighbouring natives than other non-natives - Kuebbing, Sara E. (2016)
Human activity is creating a global footprint by changing the climate, altering habitats and reshuffling the distribution of species. The movement of species around the globe has led to the naturalization and accumulation of multiple non-native species within ecosystems, which is frequently associated with habitat disturbance and changing environmental conditions. However, interactions among species will also influence community composition, but little is known about the full range of direct and indirect interactions among native and non-native species. Here, we show through a meta-analysis of 1,215 pairwise plant interactions between 274 vascular plant species in 21 major habitat types that interactions between non-native plants are asymmetrical with interactions between non-native and native plants. Non-native plants were always bad neighbours, but the negative effect of non-natives on natives was around two times greater than the effect of non-natives on other non-natives. In contrast, the performance of non-native plants was five times higher in the presence of a neighbouring native plant species than in the presence of a neighbouring non-native plant species. Together, these results demonstrate that invaded plant communities may accumulate additional non-native species even if direct interactions between non-natives species are negative. Put another way, invasions may be more likely to lead to more invasions, requiring more active management of ecosystems by promoting native species restoration to undermine invasive positive feedback and to assist native species recovery in invaded ecosystems.